2021
DOI: 10.1186/s13040-021-00273-8
|View full text |Cite|
|
Sign up to set email alerts
|

iGlioSub: an integrative transcriptomic and epigenomic classifier for glioblastoma molecular subtypes

Abstract: Background Glioblastoma (GBM) is the most aggressive and prevalent primary brain tumor, with a median survival of 15 months. Advancements in multi-omics profiling combined with computational algorithms have unraveled the existence of three GBM molecular subtypes (Classical, Mesenchymal, and Proneural) with clinical relevance. However, due to the costs of high-throughput profiling techniques, GBM molecular subtyping is not currently employed in clinical settings. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 96 publications
2
8
0
Order By: Relevance
“…Ensenyat-Mendez and co-workers constructed the iGlioSub classifier using machine learning, computational biology algorithms and prioritization of highly informative transcriptomic and epigenomic features which, based on gene expression and DNA methylation profiles, classified GBMs into classical, mesenchymal and proneural subtypes ( Figure 1 , Supplementary Table S1 ). This classifier showed better performance in stratifying patients compared to stratification based on gene expression profiles only [ 48 ].…”
Section: Molecular Gbm Subtypesmentioning
confidence: 99%
“…Ensenyat-Mendez and co-workers constructed the iGlioSub classifier using machine learning, computational biology algorithms and prioritization of highly informative transcriptomic and epigenomic features which, based on gene expression and DNA methylation profiles, classified GBMs into classical, mesenchymal and proneural subtypes ( Figure 1 , Supplementary Table S1 ). This classifier showed better performance in stratifying patients compared to stratification based on gene expression profiles only [ 48 ].…”
Section: Molecular Gbm Subtypesmentioning
confidence: 99%
“…The R/VarSelRF v0.7-8 27 package was used to identify the best gene signatures to stratify responder and non-responder patients in the training cohort. We employed VarSelRF to remove the least important features in each iteration, selecting the combination of features with the highest predictive potential, as we have previously shown [28][29][30] . This process was iterated 1,000 times to improve the classifiers, and, in each iteration, the combination of genes with the highest Area Under the Curve (AUC) was selected.…”
Section: Construction Of a Random Forest-based Classifiermentioning
confidence: 99%
“…Following publication of the original article [ 1 ], the authors identified an error in the Funding section.…”
mentioning
confidence: 99%